Sequence variation of the HVR1 region of Hepatitis C virus in response to interferon-α and ribavirin treatment - Ahmed Ali Al-Qahtani; Salvatore Rubino; Mohammed N. Al-Ahdal (Journal of Infection in Developing Countries)
Introduction: Hepatitis C virus (HCV), which is a major cause of liver diseases worldwide, undergoes genetic variation during the course of infection. The aim of this study was to examine sequence variations within the HVR1 region of HCV genotype 4 in infected Saudi patients treated with a combination therapy of interferon-α and ribavirin.